Embodied pollution and trade: a two-country general equilibrium model - Diao, Xinshen; Roe, Terry L. (1997)
The effects of environmental policy on trade and social welfare are analyzed in a modified Heckscher-Ohlin framework where pollution is embodied in a good consumed. Utility is non-homothetic to account for changes in the demand for healthy goods when income increases. If the polluting input is used intensively, taxing it alone can cause an increase in the good's level of pollution concentration. Instead, a tax on the polluting input in combination with a subsidy to the non-polluting input can result in Pareto improvement. Contrary to other approaches, an abatement policy does not necessarily have a negative effect on a country's comparative advantage. However, if the country is large, change in terms of trade may cause one country to be made better off at the expense of the other, which suggests that compensatory payments may be required to encourage abatement policies.